Pengaruh Inflasi dan Kurs Dollar Terhadap Harga Emas - Esy Delia Lewaherilla (Faculty Of Economics and Business, Musamus University, 2023)
This research uses a quantitative approach. The data used is Indonesian secondary data from January 2021 to December 2022. Data analysis techniques in this study use time series data analysis using double linear regression analysis with the help of SPSS 22.5 applications. The results of the research show that: (1) The inflation variable has a positive and significant effect on the price of gold of 0.043. (2) The exchange rate variable has a negative and significant influence on the gold price of -0,271. (3) Inflation variables and exchange rates simultaneously influence the price of gold. The value of the determination coefficient (R) in this penetration is 0.409, which means that the ability of the free variable to explain the variation of the bound variable is 40.9%, while the remaining 59.16% is described by other free variables outside the model.